Appreciative joy, nostalgia and prosocial behavior: a different approach on mental wellbeing maintenance - Jia Cheng Chong; Kususanto Ditto Prihadi; Evy Kurniasari Purwaningrum; Susanna Poay Lin Hong (International Journal of Public Health Science (IJPHS), 2022)
The effect of maintaining mental wellbeing by conducting prosocial behavior has been established for quite some time and is supported by many theories. Nevertheless, prosocial behavior might not easily be done by individuals with negative feelings due to certain emotional burdens. The current study examined the mediating effect of appreciative joy in the relationship between nostalgia and prosocial behavior. There were 123 undergraduate students with an average age of 21.2 years old recruited from a Malaysian private university using the purposive sampling method. Employing an experimental single-factor independent design; the experiment was conducted online. Multiple regression analysis showed that only the relationship between appreciative joy and prosocial behavior is statistically significant in this study, without being mediated by appreciative joy. In conclusion, nostalgia did not significantly inflict any appreciative joy that eventually drove people to conduct any prosocial behavior. Further implications and suggestions are discussed.